PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX MTs SUBULUSSALAM - Khairul Rizal; Ade Susanti; Hasmawati (Pendidikan Matematika | STKIP YM Bangko, 2021)
This study aims to determine and describe the mathematical problem solving abilities of students taught by using the learning model the power of two is better than conventional learning. The study used a quantitative approach with the experimental method. The study population was all IX grade students of Subulussalam MTs which numbered three classes with samples of class IX A as the experimental class and class IX C as the control class. The instruments used are test questions for esay mathematical problem solving abilities. The results of the data analysis requirements indicate that the data of the two sample classes are normally distributed and have homogeneous variances. Hypothesis testing uses the t-test formula. Based on the results of the analysis of research data shows that t count is greater than t table or 1.84 > 1.68 in the one-party test. Because t count > t table then Ho is rejected and Ha is accepted, so it can be concluded that the mathematical problem solving ability of the power of two learning model is better than conventional learning of IX grade students of MTs Subulussalam.